Islamic Children Literature in Digital Media as Religious Literacy Movement - Rianna Wati; Dwi Susanto (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2019)
Islamic children literature, which transformated, in new media was viewed as a part of religious movement. This movement was assumed as social reality in this era. The video children animation, Dodo and Syamil take as case. This paper explores social reality from the religous movement phenomena. Ian Watt’s sociology literary theory is used in this paper, especially the genre and the ideological expression to express social world. Data in this paper includes topic, genre, formula, and idea in the Dodo and Syamil phenomena. The data interpretation is done by relating between topic, formula, and ideological concept to find social reality. The result of this paper is that social reality based on religios islamic movement in modernity context. This movement manifested with several topic, such as faith, worship, and characters. NCR Production is a part from islamic movement which was banned by political and ideological situation.